Hak Kemerdekaan Menulis Buku dan Pencerahan Edukasi Masyarakat - Abdul wahid; Siti Marwiyah (Jurnal Konstitusi, 2011)
The verdict of the judge of the Constitutional Court is a kind of special verdict. One of the verdicts pronounced by the constitutional court judge is to approve petition. In the case of petitioner’s clain through laws number 4/PNPS/1963, the constitutional court approves the petitioner’s petition. By the constitutional court judges, this juridical product is assessed against the constitution. This verdict can be categorized into an encouragement   or support educatively, which must be welcome positively by the country pillars. Subjects being motivated to be mujtahid as a constitutional court judge are educational communities such as teachers, college students, lecturers, researchers, humanists, and knowledge admirers to become the creators in the aspect of book. In this kind of condition, it is expected that education enlightenment can be gained through the   society.